Analisis radiograf periapikal menggunakan software ImageJ pada granuloma periapikal pada perawatan endodontik - Ali Thomas; Ria Noerianingsih Firman; A. Azhari (Majalah Kedokteran Gigi Indonesia, 2017)
Analysis of periapical radiographs using ImageJ software on periapical granuloma in endodontic treatment. The assessment of the success rate of endodontic treatment on teeth with periapical granuloma is currently still using the conventional method, that is using a viewer as the tool which is then interpreted subjectively by dentist. This may lead to the possibility of signicant differences in the assessment between inter and intra-observers. The objective of this study was to demonstrate the differences in picture and the relationship of lesion size, and the number and size of trabecular particles on periapical granuloma cases before and after endodontic treatment with digitized periapical radiographs using ImageJ software. This study was conducted using observational analysis method. The sample  in this study consisted of 30 data before endodontic treatment and 30 data after endodontic treatment that had been digitized. The results of this study showed a decrease in the average size of periapical granuloma lesions from 16,400 ± 2.2924 mm2  to 13.860 ± 2.1250 mm2, an increase in the average number of particles from 70.167 ± 7.2258 to 99.733 ± 7.4089 and an increase in the particle size from 14.033 ± 1.4452 mm2 to 19.017 ± 1.4223 mm2. The conclusion of this study is that there are different pictures and relationship between the size of lesions, the number and size of trabecular particles in periapical granuloma cases before and after endodontic treatment through digitized periapical radiographs using ImageJ software.ABSTRAKPenilaian tingkat keberhasilan perawatan endodontik pada gigi yang mengalami granuloma periapikal, saat ini masih menggunakan metoda konvensional yaitu dengan menggunakan viewer sebagai alat bantu dan diinterpretasi secara subjektif oleh dokter gigi. Keadaan ini mengakibatkan peluang terjadinya perbedaan penilaian cukup besar secara inter dan intra-observer. Tujuan dari penelitian ini adalah untuk mengetahui perbedaan gambaran dan hubungan nilai luas lesi, jumlah dan luas partikel trabekula pada kasus granuloma periapikal sebelum dan sesudah perawatan endodontik melalui digitalisasi radiograf periapikal menggunakan software ImageJ. Penelitian ini dilakukan dengan menggunakan metode analisis observasional. Sampel yang digunakan dalam penelitian ini terdiri dari 30 data sebelum perawatan endodontik dan 30 data sesudah perawatan endodontik yang telah dilakukan digitalisasi. Hasil penelitian ini adalah terjadi penurunan rata-rata luas lesi granuloma periapikal dari 16.400 ± 2.2924 mm2 menjadi 13.860 ± 2.1250 mm2, peningkatan rata-rata jumlah partikel dari 70.167 ± 7.2258 menjadi 99.733 ± 7.4089 dan peningkatan luas partikel dari 14.033 ± 1.4452 mm2 menjadi 19.017 ± 1.4223 mm2. Simpulan dari penelitian ini adalah terdapat perbedaan gambaran dan hubungan nilai luas lesi, jumlah dan luas partikel trabekula pada kasus granuloma periapikal sebelum dan sesudah perawatan endodontik melalui digitalisasi radiograf periapikal menggunakan software ImageJ.